2016
DOI: 10.1177/1359105316656769
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of quality of life in patients with diabetic foot ulcer: The role of anxiety, depression, and functionality

Abstract: The goal of this study was to analyze the relationships between anxiety, depression symptoms, and functionality as predictors of quality of life, in patients with diabetic foot ulcer taking in consideration clinical variables. A sample of 202 participants indicated for a lower limb amputation surgery, were assessed before the surgery, on physical and mental quality of life, functionality, a anxiety and depression symptoms. Anxiety and depression symptoms, as well as functionality level were predictors of menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 44 publications
5
38
2
10
Order By: Relevance
“…The male predominate in 65% in the total sample and 70% on the group with ulcers. This is in agreement with the literature (Zhang et al, 2016) which indicates higher diabetic foot incidence in males (Sekhar, Thomas & Unnikrishnan, 2015;Hoban et al, 2015;Pedras, Carvalho & Pereira, 2016). Men tend to be more reluctant to seek health care, while in our study 68.3% of males were married, which permits us to deduce that they were able to count on some form of family support (Chibante, Sabóia, Teixeira & Silva, 2014;Bernini et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The male predominate in 65% in the total sample and 70% on the group with ulcers. This is in agreement with the literature (Zhang et al, 2016) which indicates higher diabetic foot incidence in males (Sekhar, Thomas & Unnikrishnan, 2015;Hoban et al, 2015;Pedras, Carvalho & Pereira, 2016). Men tend to be more reluctant to seek health care, while in our study 68.3% of males were married, which permits us to deduce that they were able to count on some form of family support (Chibante, Sabóia, Teixeira & Silva, 2014;Bernini et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In our study a patient profile similar to that in the literature was found, comprised of more elderly individuals, who had been diagnosed for longer, with low socioeconomic and education levels and, above all, who were found to have a high level of emotional suffering owing to living with diabetes when they had feet ulcers and a greater number of comorbidities. In our study, mean age of 65 years (41-83 years) was similar to that found in the literature ( Leite et al, 2015;Pedras, Carvalho & Pereira, 2016;Bernini et al, 2017). The skin of elderly people is more fragile and, in the case of people with diabetes, may be more vulnerable to the appearance of skin lesions and slower healing.…”
Section: Discussionsupporting
confidence: 91%
“…Depression, anxiety, and impaired cognition are associated with chronic wounds of multiple etiologies, including diabetic foot ulcers (DFU), venous ulcers, arterial ulcers, pressure ulcers, surgical wounds, and other traumatic wounds . A cross‐sectional large‐scale multicenter study demonstrated that the odds of depression among patients with leg ulcers were significantly higher than for patients with other skin diseases including psoriasis, atopic dermatitis, and nonmelanoma skin cancer .…”
Section: Introductionmentioning
confidence: 99%
“…Another cross‐sectional study of chronic venous ulcer patients found at least a 30% prevalence of depression and/or anxiety . Additionally, approximately 40% of DFU patients exhibit cognitive dysfunction and depression, as well as lower cognitive scores marked by decreased memorization and concentration ability, increased learning difficulties, delayed cognitive and psychomotor responses, and decreased verbal fluency when compared to age‐matched diabetic patients without chronic ulcers . Interestingly, diabetic patients who suffer from depression are twice as likely to develop a chronic foot ulcer, and depression is also a risk factor for infection in the chronic wound .…”
Section: Introductionmentioning
confidence: 99%
“…People with DM commonly present with alterations in gait biomechanics, such as reduced gait speed, decreased ankle dorsi and plantarflexion [5,9], delayed muscle activations in the leg and thigh [5,[10][11][12][13][14][15], reduced ankle and increased hip joint moments [16][17][18], and altered plantar pressure distribution patterns that increase the risk of developing plantar ulcers [19][20][21][22][23]. Due to these changes, individuals with DM may have difficulties performing their daily locomotor activities, which compromises their functionality and negatively impacts their quality of life [24][25][26].…”
Section: Introductionmentioning
confidence: 99%